Analisis Tingkat Pengetahuan Pelaku Usaha Bengkel Motor terhadap Limbah Oli dan Upaya Pengurangannya di Kota Kendari - Wa Alimuna; Asramid Yasin; Ira Ryski Wahyuni; Junartin Teke; La Ode Muhammad Erif (Fakultas Teknik, 2022)
The workshop business will produce waste that is not managed properly, it will have an impact on the environment and humans. Knowledge and attitude of workshop mechanics can influence the behaviour of workshop mechanics in managing B3 waste generated from motorcycle repair businesses. This study aims to determine the level of knowledge of mechanics, mechanical attitudes, and patterns of reducing waste in two-wheeled motor vehicle workshops in Kendari City. The method used in this research is a survey method through interviews using a questionnaire. Data analysis is by using the Gutman scale and then the results will be analysed using quantitative descriptive analysis. The results showed that the mechanics of the workshops located in Kendari City in 11 sub-districts mostly had knowledge that was in the doubtful category. Mandonga sub-districts 62%, Kambu sub-districts 61.66%, West Kendari sub-districts 38.66%, Poasia sub-districts 46.33%. Wua-Wua sub-districts 33%, and Puuwatu sub-districts 56.66%. The attitude of mechanics tends to be willing to manage B3 workshop waste, which is found in 8 sub-districts which include Abeli sub-districts 77.97%, Mandonga sub-districts 51.06%, Kambu sub-districts 63.63%, Baruga sub-districts 54.73%, Kendari sub-districts 76.47%, Puuwatu and Kadia sub-districts 57.14%, and Nambo sub-districts 70.27%. There are only 3 sub-districts that carry out the management process for B3 waste, namely Kambu sub-districts 66.66%, Kendari Barat sub-districts 58.81%, and Puuwatu sub-districts 75%.